Lysophosphatidylcholine is a Major Component of Platelet Microvesicles Promoting Platelet Activation and Reporting Atherosclerotic Plaque Instability - Diehl, Philipp; Nienaber, Frederik; Zaldivia, Maria T. K.; Stamm, Johannes; Siegel, Patrick M.; Mellett, Natalie A.; Wessinger, Marius; Wang, Xiaowei; McFadyen, James D.; Bassler, Nicole; Puetz, Gerhard; Htun, Nay M.; Braig, David; Habersberger, Jonathon; Helbing, Thomas; Eisenhardt, Steffen U.; Fuller, Maria; Bode, Christoph; Meikle, Peter J.; Chen, Yung Chih; Peter, Karlheinz (Thrombosis and Haemostasis, 2019)
Background Microvesicles (MVs) are small cell-derived vesicles, which are mainly released by activated cells. They are part of a communication network delivering biomolecules, for example, inflammatory molecules, via the blood circulation to remote cells in the body. Platelet-derived MVs are known to induce vascular inflammation. Research on the mediators and mechanisms of their inflammatory effects has attracted major interest. We hypothesize that specific lipids are the mediators of vascular inflammation caused by platelet-derived MVs.Methods and Results Liquid chromatography electrospray ionization–tandem mass spectrometry was used for lipid profiling of platelet-derived MVs. Lysophosphatidylcholine (LPC) was found to be a major component of platelet-derived MVs. Investigating the direct effects of LPC, we found that it induces platelet activation, spreading, migration and aggregation as well as formation of inflammatory platelet–monocyte aggregates. We show for the first time that platelets express the LPC receptor G2AR, which mediates LPC-induced platelet activation. In a mouse model of atherosclerotic plaque instability/rupture, circulating LPC was detected as a surrogate marker of plaque instability. These findings were confirmed by matrix-assisted laser desorption ionization imaging, which showed that the LPC concentration of human plaques was highest in vulnerable plaque regions.Conclusion LPC is a major component of platelet-derived MVs and via its interaction with G2AR on platelets contributes to platelet activation, spreading, migration and aggregation and ultimately to vascular inflammation. Circulating LPC reports on atherosclerotic plaque instability in mice and is significantly increased in unstable areas of atherosclerotic plaques in both mice and humans, linking LPC to plaque instability.
Keywords: lysophosphatidylcholine; microvesicles; platelet activation; unstable atherosclerotic plaques